Sistem Pakar Untuk Mendeteksi Kerusakan Pada Diesel Pump Dengan Metode Forward Chaining Berbasis Web - Haryadi, Haryadi; Yulia, Yulia (INNOVATICS: International Journal on Innovation in Research of Informatics, 2021)
Frequent fires can occur in or like buildings of buildings or high rise buildings. The losses incurred by the fire disaster are enormous. Care and maintenance standards for diesel engine pumps must be observed. All technicians must have expertise in the maintenance and maintenance of the diesel pump engine. Such expertise can be obtained from official training conducted by the education center, reading guidelines for dealing with diesel pump engine damage obtained from diesel pump manufacturing plants and additional knowledge gained from learning while attending education and training. In this study the researchers set "Symptoms of Damage to the diesel engine of the Fire Pump" as a variable. The expert system application detects web-based diesel pump damage with a forward chaining method that has been made, after conducting an expert analysis test then testing the user's response to this expert system application, the test is carried out by consulting using this expert system application. Expert systems are components and elements that are combined into one to achieve certain goals. The system design is done after analyzing the diesel pump damage data and designing a web-based expert system. Chaining forward method is a method of inference that makes sense from a problem to a solution. Damage to the diesel pump by using the forward chaining method provides the right solution of the problem at hand. Based on these suggestions it can be concluded that an expert system detects damage to a web-based diesel pump that has been made can help all users in analyzing the problem based on consultation